The Cultural Conflicts on E.M. Forster a Passage to India: From Post - Colonial Perspective - Shahparan, Mohammad (Riviera Publishing, 2023)
A Passage to India is an outstanding English novel from the early 20th century. This is the most successful novel written by EM Forster. Unlike other writers of fiction on colonial or postcolonial matters, Forster attempts to enrich the anti-hostile communication between British colonialists and colonized Indians in this acclaimed novel. The purpose of this study was to find out the beliefs and attitudes of British people towards non-English people that reflect cultural conflicts.This research uses a quantitative research type. Personal relations between Britain and India at the level of equality are difficult to encourage due to the superiority complex of the British and the nationalist sentiments of the Indians. The novel A Passage to India by EM Forster shows how cultural conflicts between British and Indians occurred repeatedly in India during the colonial period. The English in this novel see themselves as superior and treat the Indians with complete injustice. Finally, a British colonial presence in India was considered a very real possibility and gave rise to an ongoing cultural conflict. The novel A Passage to India, EM Forster illustrates the cultural clash between the British colonizers and the Indian colonized. The belief of British superiority over Indian culture creates a barrier to establishing personal relationships based on equality. This superiority complex and nationalist sentiment lead to cultural conflicts in India, emphasizing the damaging effects of colonialism on both colonizers and the colonized.